Corneal biomechanical properties and intraocular pressure measurement in patients with nanophthalmos. Issue 6 (7th March 2012) - Altan, Cigdem; Kara, Necip; Baz, Okkes; Şatana, Banu; Demirok, Ahmet; Yilmaz, Omer Faruk
Abstract : Aims: To compare the biomechanical properties of the cornea and intraocular pressure (IOP) between patients with nanophthalmos and age-matched controls. Methods: In this prospective, cross-sectional and comparative study, 27 eyes of 27 healthy individuals (control group) and 27 eyes of 27 patients with nanophthalmos (study group) were enrolled. Corneal hysteresis (CH), corneal resistance factor (CRF), corneal compensated intraocular pressure (IOPcc) and Goldmann correlated intraocular pressure (IOPg) were recorded for the right eye of each participant using Reichert Ocular Response Analyser measurements. Also, all participants in this study underwent a standardised ocular examination including IOP measurement with Goldmann applanation tonometry (IOPGAT ), central corneal thickness and axial length (AL) assessments. Results: Mean CH in the nanophthalmic eyes and in the control eyes were 13.3±2.4 mm Hg and 11.6±1.7 mm Hg, respectively (p=0.003); mean CRF values in the nanophthalmic and the control eyes were 13.2±1.8 mm Hg and 11.4±1.9 mm Hg, respectively (p=0.001). Mean IOPGAT was 15.2±3.3 mm Hg in the nanophthalmic eyes and 13.4±2.7 mm Hg in the control group (p=0.031); mean IOPg values for the nanophthalmic and the control groups were 17.1±5.3 mm Hg and 14.7±3.5 mm Hg, respectively (p=0.042). Mean IOPcc values in the nanophthalmic and the control group were 13.6±6.1 mm Hg and 14.8±3.2 mm Hg, respectively (p=0.365). Conclusion: The CH, CRF, IOPg and IOPGAT were significantly higher in the nanophthalmic eyes, whereas no significant differences in IOPcc were observed. These findings may be taken into account when measuring IOP values in patients with nanophthalmos.